Pelatihan Pemanfaatan Limbah Domestik agar Memiliki Nilai Ekonomis untuk Pertanian Organik di Desa Cihideung Ilir, Ciampea, Kabupaten Bogor - Nurul Jannah; R. A. Hangesti Emi Widyasari; Lesia Fatma Ginoga; Asty Syahwani (Institut Pertanian Bogor, 2023)
The high population growth rate in the Cihideung Ilir area is accompanied by a high amount of household waste, known as domestic waste. The existence of domestic waste, if utilized properly, will protect the quality of the environment since it can cause pollution. Therefore, a special effort must be made to utilize this domestic waste to be processed into a product of high economic value. In terms of the conditions, the IPB University Vocational School Lecturer Team was moved to carry out activities with farmers, cadres and residents of Cihideung Ilir Village, Ciampea, Bogor Regency to process domestic waste into Liquid Organic Fertilizer through training on utilization of domestic waste into Liquid Organic Fertilizer (LOF). This community service activity aims to provide knowledge and skills in utilizing domestic (household) waste. Farmers, cadres and local villagers attended the Training activity. The activity started with the presentation of material about LOF, the benefits of LOF and hands-on practice on how to make the Liquid Organic Fertilizer properly. The training materials were delivered directly, followed by interactive questions and answers, as well as an introduction to the tools and equipment that will be used to make organic liquid fertilizer. All the training participants actively and enthusiastically followed the discussions. The training activity for making liquid organic fertilizer is expected to reduce the amount of organic waste generated and to encourage training participants to utilize organic waste in their homes into an organic liquid fertilizer that can provide economic value. The benefits of POC from an environmental point of view can be used as fertilizer for plants in the yard or on agricultural land. From an economic point of view, it can be sold to increase residents' income.